'I am a porn star!' Sex and Sunny Leone unlimited in Bollywood. Issue 1 (2nd January 2017) - Chatterjee, Tupur
ABSTRACT: Located at the intersections of international porn studies, celebrity studies, gender, sex and globalization, this article looks at the recent and unusual case of Sunny Leone, an Indo-Canadian bisexual pornographic actress who successfully crossed over to Bollywood. By examining her many lives and avatars – as an international porn star, a reality TV contestant, a Bollywood celebrity and now a show host on MTV India, who maintains an active presence on social and digital media – I suggest that the unprecedented situation Sunny Leone has engendered in India presents us with a form of transnational onscenity: in other words, it brings to the fore the centrality of porn in the economies of global cross-cultural exchange and forces us to rethink previous paradigms of both 'pornography' and stardom, two domains that have more or less remained mutually exclusive of each other in the sub-continent. Leone's case brings to the fore economic, social and cultural exchanges between two mammoth entertainment industries, Bollywood and American pornography, which had not encountered each other in these ways before. The capital gains from these exchanges seem to overshadow concerns about preserving the nation's 'moral' fabric and have concurrently given way to newer spaces for accommodating a celebrity like Leone. Given that her crossover from porn presents an absolute rupture from all previous paradigms of female stardom in the Indian context, I place the discourses surrounding her within the tangible anxieties and fantasies of both desire and control over her 'Indian but foreign' and 'pornographic' body. Highlighting Leone's agency through the entire process, which is unique in many regards, this article attempts to further rethink and complicate overarching notions of 'objectification' that often dominate the field.